(untitled) (World Bulletin of Public Health, 2022)
The treatment results of 331 patients with ventral hernia and concomitant abdominal cavity pathology have been included in the study. Simultaneous abdominal cavity pathology requiring surgical correction in ventral hernias was 52,8%, biliary stone disease (30,1%), pelvic organs pathology in women (30,8%), adhesions of the abdomen and chronic intestinal obstruction (46,7%), and also stage III-IV obesity and abdominoptosis (29,7%) were revealed more frequently. At the location of concomitant abdominal pathology at a distance from the hernial defect (M1S8 or M3S2) the laparoscopic simultaneous stage is preferred, which was successfully carried out in 37,5% of patients, over 1/3 of patients in the main group. Optimization of tactical and technical aspects of the simultaneous surgical correction of ventral hernias and concomitant abdominal pathology with the priority use of endovideosurgical techniques and non-tension alloplasty methods permitted to decrease the incidence of postoperative complications from 8,6% to 5,3%, to reduce the duration of surgery from 72,5 ±3,4 min to 58,5 ±4,1 min and to reduce hospitalization time from 10,2±0,4 to 8,3±0,6 bed days.